A closed system for high density production of biomass - Mohamed Din, Mohamed Shariff; Md. Yusoff, Fatimah; Banerjee, Sanjoy; Khatoon, Helena (2014)
The present invention provides a closed system photobioreactor (10) for production of biomass. Accordingly, the system includes: a) a container (20) which is made up of transparent material and being transparent at all planes, such that no dark zones is formed; b) a cover (30) to allow light penetration; said cover (30) is capable of minimize any contamination, such as it prevents foreign organisms from entering the culture and to prevent water evaporation; c) at least one perforated duct (40) with plurality of apertures (42) for conveying air and carbon dioxide (CO2) into the system; d) at least one inlet (50) for hosting air and carbon dioxide (CO2) into the perforated duct (40); and e) at least one outlet (60) for culture harvesting; wherein the biomass is microalgae and/or cyanobacteria; wherein the perforated duct (40) capable to serve as control aeration in the system, such that it keeps the microalgae or cyanobacteria in suspension, and to prevent said microalgae or cyanobacteria from setting down to the base or bottom of the system; the controlled aeration also serves to prevent the microalgae or cyanobacteria from sticking to the side walls of the system; and wherein the system can be illuminated from all sides with any type of light source, including sunlight or artificial light for maximum and continuous photosynthesis.